Interpreting human rights [ social science perspectives - Morgan, Rhiannon; Turner, Bryan S. (Routledge advances in sociology, 2009)
Written by an international group of leading social science scholars in the field of human rights, this new volume situates the study of human rights in an open interdisciplinary terrain. Ranging over diverse topics and pathways in the theory and practice of human rights, this volume will be an invaluable aid to those seeking to understand the complex meanings, institutions, and practices of human rights